Drought-induced tree species replacement is reflected in the spatial variability of soil respiration in a mixed Mediterranean forest - Barba, Josep; Yuste, Jorge Curiel; Martínez-Vilalta, Jordi; Lloret, Francisco (Forest Ecology and Management, 2013)
As episodes of drought-induced forest mortality are being increasingly reported worldwide and may become more frequent in the future as a result of climate change, it is essential to characterize their functional implications in terms of ecosystem carbon and water fluxes. We investigated the spatial variability of soil respiration in a mixed Mediterranean forest located on rugged terrain, where Scots pine (Pinus sylvestris) is affected by drought-induced dieback and appears to have been replaced by Holm oak (Quercus ilex) as the dominant tree species. Soil respiration was measured in spring 2010 on two plots (16.2 × 16.2 m) using a static closed chamber method (soda lime technique) and a systematic sampling (1.8-m grid) including 100 points per plot. Biotic and abiotic variables, such as soil moisture, soil temperature, soil organic matter content, stoniness, pH, fine root C:N ratio and biomass, tree basal area and tree species and health condition of nearest neighbouring tree were also recorded. Our results showed that the spatial variability of soil respiration under optimal environmental conditions (spring) was high and showed no spatial autocorrelation on the scale studied (1–18 m). A mixed-effects model applied to explain the spatial variability of soil respiration indicated that only the variables related to forest structure (i.e., health condition and basal area) explained any of the observed variability of soil respiration (R2 = 0.45). Our model revealed that soil respiration was highest in soils close to dead pines and under Holm oak trees, suggesting that tree mortality and species replacement of pine trees by Holm oak may lead to higher soil respiration fluxes. The direct effect of tree mortality on soil respiration may be a transitory response caused by fine root mortality. Furthermore, the fact that tree species replacement as a result of drought-induced die-off is accompanied by concomitant changes in soil respiration has important implications for soil and ecosystem carbon balance
Keywords: Forest dieback; Mediterranean ecosystem; Pinus sylvestris; Quercus ilex; Soil CO2 efflux; Spatial variability

Autotrophic and heterotrophic contributions to short-term soil CO 2 efflux following simulated summer precipitation pulses in a Mediterranean dehesa - Casals, Pere; Lopez-Sangil, Luis; Carrara, Arnaud; Gimeno, Cristina; Nogués, Salvador (Global Biogeochemical Cycles, 2011)
Autotrophic and heterotrophic components of soil CO2 efflux may have differential responses to environmental factors, so estimating the relative contribution of each component during summer precipitation pulses is essential to predict C balance in soils experiencing regular drought conditions. As even small summer rains induced high instantaneous soil respiration rates in Mediterranean wooded grasslands, we hypothesized that standing dead mass, surface litter, and topsoil layer could play a dominant role in the initial flush of CO2 produced immediately after soil rewetting; in contrast, soil CO2 effluxes during drought periods should be mostly derived from tree root activity. In a grazed dehesa, we simulated four summer rain events and measured soil CO2 efflux discontinuously, estimating its d 13 C through a Keeling plot nonsteady state static chamber approach. In addition, we estimated litter contribution to soil CO2 efflux and extracted soil available C fractions (K2SO4‐extracted C and chloroform‐fumigated extracted C). The d 13 C‐CO2 from in‐tube incubated excised tree roots and rewetted root‐free soil was −25.0‰ (±0.2) and −28.4‰ (±0.2), respectively. Assuming those values as end‐members’ sources, the autotrophic component of soil CO2 efflux was dominant during the severe drought, whereas the heterotrophic contribution dominated from the very beginning of precipitation pulses. As standing dead mass and fresh litter contribution was low (<25%) in the first day and negligible after, we concluded that CO2 efflux after rewetting was mostly derived from microbial mineralization of available soil organic C fractions.
Keywords: d13C; Drought; precipitation manipulation (voyant); Soil CO2 efflux

Evaporation and carbonic anhydrase activity recorded in oxygen isotope signatures of net CO2 fluxes from a Mediterranean soil - Wingate, Lisa; SEIBT, ULLI; MASEYK, KADMIEL; OGÉE, JÉRÔME; Almeida, Pedro; YAKIR, D. A. N.; Pereira, João S.; MENCUCCINI, MAURIZIO (Global Change Biology, 2008)
The oxygen stable isotope composition (δ18O) of CO2 is a valuable tool for studying the gas exchange between terrestrial ecosystems and the atmosphere. In the soil, it records the isotopic signal of water pools subjected to precipitation and evaporation events. The δ18O of the surface soil net CO2 flux is dominated by the physical processes of diffusion of CO2 into and out of the soil and the chemical reactions during CO2–H2O equilibration. Catalytic reactions by the enzyme carbonic anhydrase, reducing CO2 hydration times, have been proposed recently to explain field observations of the δ18O signatures of net soil CO2 fluxes. How important these catalytic reactions are for accurately predicting large-scale biosphere fluxes and partitioning net ecosystem fluxes is currently uncertain because of the lack of field data. In this study, we determined the δ18O signatures of net soil CO2 fluxes from soil chamber measurements in a Mediterranean forest. Over the 3 days of measurements, the observed δ18O signatures of net soil CO2 fluxes became progressively enriched with a well-characterized diurnal cycle. Model simulations indicated that the δ18O signatures recorded the interplay of two effects: (1) progressive enrichment of water in the upper soil by evaporation, and (2) catalytic acceleration of the isotopic exchange between CO2 and soil water, amplifying the contributions of ‘atmospheric invasion’ to net signatures. We conclude that there is a need for better understanding of the role of enzymatic reactions, and hence soil biology, in determining the contributions of soil fluxes to oxygen isotope signals in atmospheric CO2.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: atmospheric invasion; carbonic anhydrase; Drought; Mediterranean forests; oxygen isotopes; Quercus suber; Soil CO2 efflux; soil evaporation; soil water δ18O composition

Evaporation and carbonic anhydrase activity recorded in oxygen isotope signatures of net CO2 fluxes from a Mediterranean soil - Wingate, Lisa; SEIBT, ULLI; MASEYK, KADMIEL; OGÉE, JÉRÔME; Almeida, Pedro; YAKIR, D A N; Pereira, João S; MENCUCCINI, MAURIZIO (Global Change Biology, 2008)
The oxygen stable isotope composition (δ18O) of CO2 is a valuable tool for studying the gas exchange between terrestrial ecosystems and the atmosphere. In the soil, it records the isotopic signal of water pools subjected to precipitation and evaporation events. The δ18O of the surface soil net CO2 flux is dominated by the physical processes of diffusion of CO2 into and out of the soil and the chemical reactions during CO2–H2O equilibration. Catalytic reactions by the enzyme carbonic anhydrase, reducing CO2 hydration times, have been proposed recently to explain field observations of the δ18O signatures of net soil CO2 fluxes. How important these catalytic reactions are for accurately predicting large-scale biosphere fluxes and partitioning net ecosystem fluxes is currently uncertain because of the lack of field data. In this study, we determined the δ18O signatures of net soil CO2 fluxes from soil chamber measurements in a Mediterranean forest. Over the 3 days of measurements, the observed δ18O signatures of net soil CO2 fluxes became progressively enriched with a well-characterized diurnal cycle. Model simulations indicated that the δ18O signatures recorded the interplay of two effects: (1) progressive enrichment of water in the upper soil by evaporation, and (2) catalytic acceleration of the isotopic exchange between CO2 and soil water, amplifying the contributions of ‘atmospheric invasion’ to net signatures. We conclude that there is a need for better understanding of the role of enzymatic reactions, and hence soil biology, in determining the contributions of soil fluxes to oxygen isotope signals in atmospheric CO2.
Keywords: atmospheric invasion; carbonic anhydrase; Drought; Mediterranean forests; oxygen isotopes; Quercus suber; Soil CO2 efflux; soil evaporation; soil water δ18O composition